Cranberry for Bacteriuria in Individuals with Spinal Cord Injury: A Systematic Review and Meta-Analysis. (31st October 2020) - Raguzzini, Anna; Toti, Elisabetta; Sciarra, Tommaso; Fedullo, Anna Lucia; Peluso, Ilaria
Abstract : Background . Urinary tract infection (UTI) is common in individuals with spinal cord injury (SCI) and neurogenic lower urinary tract dysfunction (NLUTD) and in veterans with SCI who use antibiotics improperly for asymptomatic bacteriuria. Cranberry (CB) has been suggested for UTI prevention. Methods . We performed a systematic search up to May 2020 in the following databases: AccessMedicine, BioMed Central, CINAHL, Cochrane Library, ProQuest, and PubMed. Quality assessment was performed using a specifically designed quality score. Risk ratio was calculated with both random effect model analysis (DerSimonian-Laird method) and quality effect model analysis (Doi Thalib method). Results . Six studies on bacteriuria and SCI were reviewed. From the four studies available for meta-analysis, two of which with individuals taking both CB and control, 477 data from 415 participants were analysed (241 CB and 236 control). No significant differences were detected with meta-analysis. However, bias, limitations, and incompleteness were observed in the reviewed studies. Conclusion . Although further studies are needed, we suggest an accurate monitoring of diet and fluid intake, the evaluation of risk for potential food or nutraceutical interactions with drugs, and the inclusion of inflammatory markers among the outcomes in addition to UTI.